Assessing the prevalence of Staphylococcus aureus in (UTIs) patients age groups - Salimah M. Alsuwayah; A. R. Elkhouly; Mohamed O. Albasha (African Journal of Advanced Pure and Applied Sciences, 2026)
Background: Staphylococcus aureus, a bacterium of significant clinical importance, is recognized as the etiological agent responsible for an extensive array of infections that can affect both individuals receiving outpatient care as well as those who are admitted to hospitals for medical treatment. This particular microorganism is widely acknowledged as one of the most prevalent contributors to the incidence of nosocomial infections, which are infections acquired in hospital settings, across numerous healthcare facilities in various countries situated around the globe. Objectives: the primary objective of the research being conducted in this study is to meticulously assess and analyze the prevalence and distribution of the bacterium Staphylococcus aureus within the context of urinary tract infections (UTIs) among patients of varying ages and sexes within the designated geographical area under investigation. Methods: The present investigation was meticulously carried out at the Sabratha Central Hospital over an extensive timeframe spanning from September to November 2025., during which a comprehensive analysis was undertaken. The biological samples were systematically collected from a cohort of patients diagnosed with urinary tract infections (UTIs), comprising a total of 572 individuals, among which 377 were identified as females and 195 as males, all of whom were duly registered participants in this particular research endeavor, and both urine and semen samples were acquired under strictly aseptic conditions to ensure the integrity of the subsequent microbial culture analyses. Furthermore, the patients involved in this study were categorized into a total of 17 distinct age groups, allowing for a nuanced examination of the data across various demographic segments. Results: A comprehensive analysis involving 572 patients, comprising 377 females and 195 males, was performed with urine samples cultured on CLED agar for microbiological assessment. In female samples, The age group 21-25 showed the highest infection rate at 19.84%, followed by 26-30 years at 16.79%, highlighting the prevalence of urinary tract infections in these demographics. In male samples, the 0-5 years age group had the highest infection rate at 37.75%, succeeded by the 6-10 years group at 7.14% of positive samples collected. A meticulous analysis of 69 male patients undergoing semen analysis involved culturing samples on CLED agar for microbiological evaluation, revealing 21 samples with positive microbial growth. The age group 36-40 demonstrated the highest infection rate at 33.33%, followed by 26-30 years at 28.57%, emphasizing significant public health implications.